Pelatihan Pemanfaatan Teknologi Informasi sebagai Upaya Peningkatan Kompetensi Digital Remaja di Desa Aikmel Utara - Siti Marhamah; Siti Sa’adah; Taufik Rauhul Hidayat; Ida Wahidah; Hadian Mandala Putra (Universitas Hamzanwadi, 2026)
Low access to technology education remains a primary obstacle for rural youth in facing the challenges of the digital era. This community service program aims to enhance the digital literacy of children and teenagers in North Aikmel Village through a structured IT training program. The program was implemented using a systematic five-step method consisting of introduction, basic training, practical practice, discussion, and evaluation. This intensive training involved 32 participants, divided into a children's group (18 participants) and a youth group (14 participants). The results indicated a significant increase in capability; the children's group successfully mastered Microsoft Word for school administration, while the teenagers understood Python programming logic and basic Artificial Intelligence (AI) concepts by creating a cashier system simulation and utilizing the innovative PyLearn for AI platform. The integration of face-to-face training and digital infrastructure proves effective in creating an adaptive education system at the village level, reducing the digital divide, and establishing a sustainable digital legacy for the community